State Behavior and Regional Identity: The Case of China and East Asia - Littlefield, Alex (Animo Repository, 2012)
The research on East Asian multilateralism argues favorably or unfavorably over the effectiveness and durability of regional cooperation towards strengthening state-to-state relations. Those who locate cooperation (e.g. economic or security) and shared norms among Asian neighbors typically apply a liberal institutionalist or a social constructivist approach. Those who doubt the depth and authenticity of corporate spirit and goodwill towards regionalization speak in terms of traditional power politics and strategic balancing. This paper critically examines Asian regionalism using the language of social constructivism and not political realism. Ideas, identities, perceptions, and behavior are prioritized and material forces are of less concern except to the degree they influence identity. Particularly, China’s behavior will have the greatest impact, rather than current regional norms, on the viability of East Asian regionalization.